Thermodynamics - Klein, Sanford A. , 1950-; Nellis, Gregory (New York : Cambridge University Press, 2012)
"The objective of this comprehensive text is to provide engineers with the concepts, tools, and experience needed to solve practical real-world energy problems using modern computing tools"
1. Basic concepts -- 2. Thermodynamic properties -- 3. Energy and energy transport -- 4. General application of the first law -- 5. The second law of thermodynamics -- 6. Entropy -- 7. Exergy -- 8. Power cycles -- 9. Refrigeration and heat pump cycles -- 10. Property relations for pure fluids -- 11. Mixtures and multi-component phase equilibrium -- 12. Psychometrics -- 13. Combustion -- 14. Chemical equilibrium -- 15. Statistical thermodynamics -- 16. Compressible flow
Keywords: Engineering -- Problems, exercises, etc; Thermodynamics